Differences in the relative roles of environment, prey availability and human activity in the spatial distribution of two marine mesopredators living in highly exploited ecosystems. (20th October 2015) - Navarro, Joan; Cardador, Laura; Fernández, Ángel M.; Bellido, José M.; Coll, Marta
Abstract: Aim: Identifying the main factors affecting the spatial distribution of marine predators is essential in order to evaluate their distribution patterns, predict the potential impact of human activities on their populations and design accurate management actions. This information is also valuable from a more general management perspective, as marine predators are often considered indicators of habitat quality. In this context, we aimed to determine the degree to which environmental features, prey availability and human activities interact and influence spatial distribution of two marine mesopredator elasmobranchs, the small‐spotted catshark ( Scyliorhinus canicula ) and the Mediterranean starry ray ( Raja asterias ), living in a highly human‐exploited environment. Location: Mediterranean Sea. Methods: With information obtained from an extended experimental survey, we investigated the relative importance of environmental variables, prey availability and human activities on the spatial distribution of the abundance, biomass and occurrence rate of these marine mesopredators using deviance partitioning analyses. Results: Our results revealed that environmental variables were the most important factors explaining the spatial distribution of Mediterranean starry ray, whereas small‐spotted catshark distribution was also influenced by prey availability and human factors. From a management point of view, these findings suggest that Mediterranean starry ray could be a good candidate as an indicator species of demersal environmental quality. On the other hand, the distribution of the small‐spotted catshark, which responds in an interactive and complex way to environment, prey availability and particular human activities, may be misleading as an environmental indicator. Main conclusions: The spatial distribution of elasmobranchs in highly human‐impacted marine areas can reflect the interactive and combined effects of multiple factors. To avoid misunderstandings, attention should be paid to statistical procedures allowing the separation of pure and joint contribution of the factors driving the observed spatial patterns.